Turning Meadow Weeds Into Valuable Species for the Romanian Ethnomedicine While Complying With the Environmentally Friendly Farming Requirements of the European Union’s Common Agricultural Policy - Grosu, Elena; Ichim, Mihael Cristin (Frontiers in Pharmacology, 2020)
The cross-compliance mechanism of the European Union (EU)'s common agricultural policy (CAP) makes the approval of the direct payments to the European farmers subject to compliance with the requirement to maintain the land in good agricultural and environmental condition. One of the obligations of the Romanian land owners and farmers is to avoid the installation of unwanted vegetation on their land plots. This vegetation is represented by some species of herbaceous or woody plants, annual or perennial, that spontaneously invade the agricultural lands, diminishing the production capacity of the cultivated plants. Included in this category are 10 meadow weeds, without fodder value or even toxic to animals: Arctium lappa L., Carduus nutans L., Conium maculatum L., Eryngium campestre L., Euphorbia cyparissias L., Pteridium aquilinum (L.) Kuhn, Rumex acetosella L., Veratrum album L., Xanthium spinosum L., and Xanthium strumarium L. Various and multiple uses in traditional medicine of these meadow weed species have been reported for Romania and other nine neighboring East European countries, i.e. Bosnia and Herzegovina, Bulgaria, Czech Republic, Estonia, Kosovo, Russia, Turkey, Serbia, and Ukraine. For A. lappa were recorded the highest number of ethnomedicinal uses, in the largest number of East European countries, including Romania. C. maculatum and V. album are not recommended for human consumption but can be further investigated as potential sources of pharmaceutically active compounds. Once removed by landowners and farmers from their land, the raw plant material of these 10 species become readily and easily available to the Romanian local communities and the industry of herbal food supplements, while the biodiversity of the agro-ecosystems is maintained.